Mononuclear Dioxomolybdenum(VI) and Dioxotungsten(VI) Complexes with Di(1-Phenyl Tetrazoline)-5,5’-Disulphie - Pandey, R.N.; Rani Kumari, Mrs.; Kumar, Narendra (Asian Journal of Chemistry, 2012)
Di (1-phenyl tetrazoline)-5,5'-disulphie (TDS) forms very stable complexes with MO22+ species (M = Mo or W) having general formula (MO2(TDS)2Cl2] and [MO2(TDS)4]Cl2. The disulphide ligand interacts with MO22+ species through one of the disulphide sulphur atoms. All the complexes are distorted octahedral structure in which two oxygen atoms are cis in MO2 group and two bulky ligands are at trans dispositions.